PERANAN PENDIDIKAN LUAR BIASA DALAM PEMBINAAN ANAK TUNAGRAHITA: Studi pada Sekolah Luar Biasa (SLB) C Dharma Bakti Pertiwi Bandar Lampung - MUHASSIN, MOHAMMAD (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2015)
The study entitled  "The Role of Special Education  in the Development of Mentally Retarded Children: Studies in special  school (SLB) of Dharma Bakti Pertiwi Bandar Lampung" aims to analyze and describe the roles owned by  SLB C Dharma Bakti Pertiwi Bandar Lampung in coaching Mentally Retarded Children. This type of research is descriptive-qualitative with primary and secondary data sources. Primary data are obtained through observation and interviews with informant based on a purposive sampling technique. Meanwhile, secondary data are  the data obtained from documentation in the form of journals, newspapers, magazines, and the documents required. The results shows  that the roles held by SLB C Dharma Bakti Pertiwi Bandar Lampung in coaching Mentally Retarded Children  are divided into four types, namely (1) instilling behavioral affection, (2) developing the cognitive abilities, (3) developing language skills, and (4) training the adaptive skills. Keywords: special education, child development, mentally retarded                    children